Evaluación de ruido ambiental en alrededores a centros médicos de la localidad Barrios Unidos, Bogotá - Chaux Alvarez, Laura Maria; Acevedo Buitrago, Baudilio (Revista Científica, 2019)
In the present project, environmental noise assessment is carried out in the vicinity of three medical centers located in the town of Barrios Unidos (Bogotá), with the objective of determining compliance with the maximum permissible limits for this type of sectors classified as tranquility and silence, and verify the influence of the development and growth of the locality on the potential impact on the health of people. The methodology developed for the measurement processes in the different medical centers is based on the guidelines given in Resolution 627 of 2006 of the Ministry of Environment. In this way, it was carried out by each medical center; georeferencing of the study area, and preliminary measurements, which allowed establishing the existence of noise pollution and locating a point of greater impact in which the definitive measurements were made. At the same time, meteorological data was taken, as well as a characterization of vehicular traffic to build noise maps using SoundPlan software. The results obtained in each medical center generally demonstrate that the regulatory limits of environmental noise are exceeded, and this phenomenon is mainly correlated with the high traffic of vehicles, the concurrence of people talking and the informal and formal commercial activities that have developed in a disorderly around the location of hospital centers, becoming a commercial environment and generating that there is no compliance with the ordering plan established in the locality.